Manufacturing method of compression bonded magnets
Patent Information
- Application Number
- JP2021061951
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-03-31
- Publication Date
- 2025-03-06
- Estimated Expiration
- 2041-03-31
AI Technical Summary
【0012】 (2)本発明の製造方法によれば、圧縮力を増大させるまでもなく、配向磁場の低減または遮断(「遮断等」という。)により、圧縮ボンド磁石(単に「ボンド磁石」という。)の高密度化が図られる。逆に、所望の配向度と密度を有するボンド磁石を、圧縮力を低減させつつ成形することが可能となる。圧縮力の低減により、例えば、キャビティを構成する金型·筐体の変形抑制、ボンド磁石の精度向上または磁石粒子の割れ抑制等も可能となり得る。
Smart Images

Figure 0007640843000001 
Figure 0007640843000002 
Figure 0007640843000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for producing a compression bonded magnet. [Background technology]
[0002] Rare earth magnets are widely used in electromagnetic devices (electric motors, etc.) to improve performance and save energy. There are two types of rare earth magnets: sintered magnets made by sintering rare earth magnet powder, and bonded magnets made by binding rare earth magnet powder with a binder resin. Bonded magnets have better moldability and greater freedom in shape than sintered magnets.
[0003] Bonded magnets are mainly classified into injection bonded magnets, which are formed by injecting a molten mixture of magnet powder and thermoplastic resin into a cavity of a housing (such as a slot in a rotor core) and molding it as a single unit, and compression bonded magnets, which are formed by compressing a mixture or kneaded product of magnet powder and thermosetting resin in a cavity of a mold, housing, etc. Compression bonded magnets usually use a thermosetting resin as the binder resin, so they have better heat resistance than injection bonded magnets. The following Patent Document 1 describes a method for manufacturing such compression bonded magnets. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] Japanese Patent Application Publication No. 8-31677 Summary of the Invention [Problem to be solved by the invention]
[0005] Patent Document 1 proposes a method for manufacturing a magnetically anisotropic resin-bonded magnet (simply called a "bonded magnet"). The specific steps are as follows (see, for example,
[0024] and
[0065] of Patent Document 1).
[0006] First, the raw powder, which is a mixture of magnet powder and thermosetting resin (epoxy resin) powder (simply referred to as "resin powder"), is fed into a heated molding die (die temperature: 150°C). Next, once the resin powder has melted, the application of a magnetic field (16 kOe) is started, and once the molten resin has reached its minimum viscosity, pressure (8 ton / cm) is applied. 2 ) to start.
[0007] After that, the cross-linking reaction of the liquid resin progresses, and when its viscosity increases, the application of the magnetic field, heat and pressure are stopped and the bonded magnet is removed from the molding die. The bonded magnet is then subjected to a heat hardening process (cure process) at the same temperature as the die temperature.
[0008] In the hot magnetic field molding of Patent Document 1, an intentional time lag is set between the start of magnetic field application and the start of pressure application. However, there is no significant time lag set between the end of magnetic field application and the end of pressure application. In other words, in the case of Patent Document 1, the end of magnetic field application and the end of pressure application are almost simultaneous.
[0009] The present invention has been made in view of the above circumstances, and has an object to provide a new method for producing a compression bonded magnet that differs from conventional methods. [Means for solving the problem]
[0010] As a result of extensive research, the inventors have discovered that it is possible to increase the density of bonded magnets by reducing or cutting off the aligning magnetic field during the molding process of heating and compressing. By expanding on this finding, the inventors have completed the present invention, which will be described below.
[0011] <Manufacturing method of compression bonded magnets> (1) The present invention is a method for producing a compressed bonded magnet, comprising a molding step of heating and compressing a bonded magnet raw material consisting of magnet powder and a binder resin capable of binding the magnet powder in a cavity, wherein the magnet powder includes anisotropic magnet powder and the binder resin includes a thermosetting resin, and the molding step has a first molding step performed while applying an aligning magnetic field into the cavity, and a second molding step performed after the first molding step by reducing or blocking the aligning magnetic field.
[0012] (2) According to the manufacturing method of the present invention, the density of the compressed bonded magnet (simply referred to as "bonded magnet") can be increased by reducing or blocking (referred to as "blocking, etc.") the aligning magnetic field without the need to increase the compressive force. Conversely, it is possible to mold a bonded magnet with the desired degree of orientation and density while reducing the compressive force. By reducing the compressive force, it may be possible, for example, to suppress deformation of the mold and casing that form the cavity, improve the precision of the bonded magnet, or suppress cracking of the magnet particles.
[0013] Compression bonded magnets / magnetic components The present invention can also be understood as a compression bonded magnet obtained by the above-mentioned manufacturing method. The present invention can also be understood as a magnetic member in which a compression bonded magnet is integrated with a housing having a cavity. An example of a magnetic member (electromagnetic member, etc.) is a field element.
[0014] The field element is, for example, the rotor or stator of an electric motor. Electric motors include not only motors but also generators. The electric motor may be a DC motor or an AC motor. When the field element is a rotor, for example, the housing is a rotor core and the cavity is its slot. The rotor may be an inner rotor or an outer rotor.
[0015] "others" Unless otherwise specified, "x to y" in this specification includes a lower limit value x and an upper limit value y. Any numerical value included in the various numerical values or numerical ranges described in this specification may be used as a new lower limit value or upper limit value to create a new range such as "a to b". Furthermore, unless otherwise specified, "x to y MPa" in this specification means x MPa to y MPa. The same applies to other unit systems (μm, etc.). [Brief description of the drawings]
[0016] [Figure 1A] 3A to 3C are explanatory diagrams illustrating each process of heating and magnetic field molding. [Figure 1B] 1 is a time chart of the compression force and the aligning magnetic field during molding. [Figure 1C] 1 is a graph showing the change over time in viscosity of a thermosetting resin. [Figure 1D] 1 is a graph showing the relationship between compression force (molding pressure) and density of a bonded magnet when molding is performed without a magnetic field and when molding is performed in a magnetic field. [Figure 1E] FIG. 2 is a schematic diagram for explaining the effect on the density of a bonded magnet of the presence or absence of a magnetic field applied during molding. [Diagram 2] FIG. 1 is a scatter plot showing the effect of different molding methods on the density of bonded magnets for each compression force. [Figure 3A] FIG. 1 is a scatter plot showing the relationship between the end of application of an aligning magnetic field and the density, degree of orientation, or residual magnetic flux density of a bonded magnet (compressive force: 20 MPa). [Figure 3B] FIG. 1 is a scatter plot showing the relationship between the end of application of an aligning magnetic field and the density, degree of orientation, or residual magnetic flux density of a bonded magnet (compressive force: 30 MPa). [Figure 4] This is a photograph of the exterior of an IPM rotor in which bonded magnets are integrally molded into the slots. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0017] One or more components selected from the items described in this specification may be added to the above-mentioned configuration of the present invention. The components may be related to the manufacturing method or the product. Which embodiment is best depends on the target, required performance, etc.
[0018] 《Forming in heated magnetic field》 An overview of the hot magnetic field molding according to the present invention and the mechanism by which it is possible to achieve high density and the like of a bonded magnet will be described with reference to Figs. 1A to 1E (collectively referred to as "Fig. 1").
[0019] (1) Overview The heated magnetic field molding of bonded magnets is carried out in order through each process (step) shown in Figure 1A. Each step is as follows: Raw material consisting of magnet powder and binder resin (mainly thermosetting resin) is supplied (put in, housed, etc.) into a cavity of a heated metal mold or the like (supply step). Figure 1A shows an example of a case where the cavity is formed by a die and upper and lower punches. Unless otherwise specified, heating continues from the start of molding (when raw material is supplied) to the end of molding (when the bonded magnet is removed).
[0020] After the binder resin (particularly thermosetting resin / simply referred to as "resin") begins to melt in the cavity, an aligning magnetic field is applied (alignment process). However, raw material may be supplied into the cavity while the aligning magnetic field is being applied. In other words, the order in which the raw material is supplied and the aligning magnetic field is applied does not matter, and both may be applied simultaneously. It is preferable to apply an aligning magnetic field after the compound is supplied, as this allows the compound to be introduced into the cavity without being affected by the magnetic field.
[0021] The raw material that has been heated and subjected to a magnetic field is compressed (pressurized) (orientation compression process). After that, while continuing the compression, the aligning magnetic field is shut off (compression process).
[0022] The time-dependent changes (time chart) of the aligning magnetic field (H) and compressive force (P) applied to the raw material are shown in Fig. 1B. In the hot magnetic field compaction according to the present invention, a significant time difference (Δt) is intentionally set not only between the start of magnetic field application (t1) and the start of compression (t2), but also between the end of magnetic field application (t3) and the end of compression (t4).
[0023] (2) Mechanism The reason why a highly oriented, high density bonded magnet can be obtained by the orientation compression process (corresponding to the first compaction process) and the compression process (corresponding to the second compaction process) is thought to be as follows.
[0024] First, the resin heated in the cavity melts and becomes liquid. As shown in Figure 1C, its viscosity initially decreases monotonically with time, reaches a minimum (extremely small), and then increases monotonically. If heating is continued, the resin will thermally harden and become solid. Note that the viscosity change of the raw materials (magnetic particles and resin) usually follows a similar trend to that of the resin.
[0025] Next, the density of a bonded magnet obtained by applying an aligning magnetic field and heating and compressing the raw material (called "magnetic field molding") and the density of a bonded magnet obtained by heating and compressing the raw material without applying an aligning magnetic field (called "magnetic field free molding") are, for example, as shown in Figure 1D. In either case, the density of the bonded magnet increases with increasing compression force. However, when viewed at the same compression force, a bonded magnet molded without a magnetic field has a higher density than a bonded magnet molded in a magnetic field.
[0026] It is not clear why the density of a bonded magnet changes with or without an aligning magnetic field (H) even with the same compression force (P), but the results suggest the following. As shown in Figure 1E, when molding in a magnetic field, a stronger magnetic attraction force acts in the direction of the aligning magnetic field (H) between the magnet particles and the inner wall surface of the cavity or between adjacent magnet particles, due to the aligning magnetic field. Under these circumstances, when a compressive force perpendicular to the aligning magnetic field (H) acts on a compound consisting of magnet powder and binder resin, a friction force (f) proportional to the magnetic attraction force is generated between the inner wall surface of the cavity and the magnet particles, or between the magnet particles themselves. Due to this friction force, magnet particles molded in a magnetic field are more restricted in changing their posture and moving in the compression direction than magnet particles molded without a magnetic field. As a result, it is thought that the density of a bonded magnet decreases when molded in a magnetic field compared to when molded without a magnetic field.
[0027] By going through the orientation compression process and compression process as in the present invention, the above-mentioned viscosity change of the resin and the effect on density by the orientation magnetic field act additively or synergistically to obtain a highly oriented, high-density bonded magnet. Specifically, first, in the orientation compression process, the magnetic particles in the resin with reduced viscosity undergo sufficient posture change (movement, rotation, etc.) along the orientation magnetic field, achieving high orientation. Next, in the compression process, compression is performed without resistance caused by the orientation magnetic field, achieving high density.
[0028] The timing for cutting off the aligning magnetic field (starting the compression process (second molding step)) should be near the point where the viscosity of the molten resin becomes minimal. If this timing is too early, it may result in a decrease in the degree of orientation. If this timing is too late, the increase in density will be insufficient.
[0029] 《Molding process》 The compression force may be high as in the past, or may be low. To obtain a more sufficient effect, the compression force may be low, such as 5 to 50 MPa or even 10 to 40 MPa. By reducing the compression force, cracking of the magnet particles and deformation of the housing that constitutes the cavity can be suppressed.
[0030] The compression force in the first molding process and the second molding process may be the same or different. For example, if the compression force is constant, the pressure device and pressure control can be simplified. The compression force in the second molding process, where the viscosity of the resin has already increased sufficiently, may be made greater than the compression force in the first molding process to further increase the density of the bonded magnet.
[0031] The heating temperature during the molding process is adjusted according to the properties of the binder resin (particularly the thermosetting resin). The heating temperature is, for example, 100 to 200°C, 120 to 180°C, or even 130 to 170°C. If the heating temperature is too low, the resin may not soften or melt sufficiently, resulting in a decrease in the degree of orientation or density. If the heating temperature is too high, the magnet particles may be oxidized and deteriorated, and the thermosetting resin may harden prematurely.
[0032] The aligning magnetic field during the molding process is usually applied in an aligning direction that intersects (or is even perpendicular to) the compression direction of the bonded magnet raw material. The magnitude of the aligning magnetic field is, for example, 0.5 to 3 T, or even 1 to 2 T. The aligning magnetic field is the magnetic flux density on the inner peripheral surface of the cavity in which the bonded magnet is molded. In addition to electromagnets, rare earth permanent magnets may also be used as the magnetomotive source of the aligning magnetic field.
[0033] Bonded magnet raw materials The bonded magnet raw material may be a compound or a preform of a compound.
[0034] The compound is made of granules obtained by mixing or kneading (referred to as "mixing, etc.") magnet powder and binder resin. Mixing, etc. is preferably performed at a temperature at least equal to or higher than the temperature at which the binder resin softens (softening point), but lower than the temperature at which the thermosetting resin contained in the binder resin hardens too rapidly. Depending on the type and composition of the binder resin (especially the thermosetting resin), the temperature is, for example, 40 to 120°C, or even 80 to 100°C.
[0035] The bonded magnet raw material should be prepared by mixing under conditions that are unlikely to cause damage such as cracks to the magnet particles. Specifically, the magnet powder and binder resin should be mixed under conditions where pressure (shear stress) is not very effective. For example, a batch-type kneader can be used for mixing. In this case, the amount of bonded magnet raw material put in should be 75% or less, or even 65% or less of the processing volume of the processing tank, and the raw material should be heated and mixed by rotating the blades without applying pressure.
[0036] The preform consists of a block of the above-mentioned compound in a specified form (shape, size). If the preform has a form similar to that of a bonded magnet, it can be efficiently accommodated (put into) the cavity. The preform may also have a form dissimilar to that of a bonded magnet. For example, it may be a finely divided body (pellets, etc.) within the range that can be filled or loaded into the cavity. In this case, there is no need to prepare a dedicated preform for each bonded magnet, which increases the versatility of the preform.
[0037] The preforming process should also be carried out under conditions that are unlikely to cause damage such as cracks to the magnet particles. Preforming is usually carried out by pressurizing a compound filled in a cavity separate from the cavity in which the bonded magnet is molded.
[0038] 《Magnetic Powder》 The magnetic powder may be, for example, 60-80 volume %, 65-75 volume %, or even 68-73 volume % of the total bonded magnet raw material (bonded magnet) (total of magnetic powder and binder resin). If there is too little magnetic powder, the magnetic properties of the bonded magnet may deteriorate, and if there is too much magnetic powder, the degree of orientation or density may decrease.
[0039] The magnet powder may be a single type of powder or multiple types of powder as long as it contains anisotropic magnet powder (particles). Multiple types of powder are, for example, a mixed powder in which powders differ in at least one of morphology (particularly particle size), component composition, and magnetic properties (including irreversible demagnetization) are mixed.
[0040] As an example, a mixed powder containing a coarse powder and a fine powder having different average particle sizes may be used. The average particle size of the coarse powder is, for example, 40 to 200 μm, or 80 to 160 μm. The average particle size of the fine powder is, for example, 1 to 10 μm, or 2 to 6 μm. The average particle size referred to in this specification is determined by measurement using a laser diffraction type particle size distribution measuring device (HELOS manufactured by Nippon Laser Corporation).
[0041] The volume ratio of the coarse powder to the total of the coarse powder and the fine powder (or the entire magnet powder) is, for example, 60 to 90 volume %, or 65 to 85 volume %. In other words, the volume ratio of the fine powder to the total is, for example, 10 to 40 volume %, or 15 to 35 volume %.
[0042] By keeping the particle sizes and ratios of the coarse powder and fine powder, and the amount of magnet (amount of resin) relative to the entire bonded magnet raw material (bonded magnet) within specified ranges, a high-density bonded magnet can be obtained even when molded at low pressure.
[0043] The magnet powder used may be, for example, hydrogen-treated rare earth anisotropic magnet powder. Hydrogenation mainly involves a disproportionation reaction caused by hydrogen absorption (also simply called the "HD reaction") and a recombination reaction caused by desorption (also simply called the "DR reaction"). The HD reaction and the DR reaction are collectively referred to simply as the "HDDR reaction." Furthermore, the hydrogen treatment that produces the HDDR reaction is simply referred to as "HDDR (treatment)."
[0044] In addition, unless otherwise specified, HDDR as used in this specification also includes an improved type, d-HDDR (dynamic-Hydrogenation-Disproportionation-Desorption-Recombination). d-HDDR is described in detail, for example, in International Publication WO2004 / 064085.
[0045] An example of the coarse powder is NdFeB anisotropic magnet powder, the base components of which are Nd, Fe, and B. An example of the fine powder is SmFeN anisotropic magnet powder, the base components of which are Sm, Fe, and N, or SmCo anisotropic magnet powder, the base components of which are Sm and Co. As the fine powder (part), NdFeB anisotropic magnet powder with particle size adjustment may be used.
[0046] As part of the magnet powder, magnet powders other than rare earth anisotropic magnet powder (rare earth isotropic magnet powder, ferrite magnet powder, etc.) may be included. In this specification, the base component can be rephrased as an essential component or a main component. The total amount of the elements that make up the base component is usually 80 atomic % or more, or even 90 atomic % or more, of the entire target object (magnet particles). The rare earth magnet powder may contain elements that increase its coercivity, heat resistance, etc. (heavy rare earth elements such as Dy and Tb, Cu, Al, Co, Nb, etc.).
[0047] <Binder resin> The binder resin includes a thermosetting resin. Thermosetting resins include epoxy resin, phenol resin, melamine resin, urea resin, unsaturated polyester resin, etc. A typical epoxy resin is usually a mixture of a base resin (prepolymer) and a curing agent, and hardens by forming a crosslinked network with epoxy groups. Examples of epoxy resin prepolymers include novolac type, bisphenol A type, bisphenol F type, biphenyl type, naphthalene type, aliphatic type, and glycidyl amine type. Examples of epoxy resin curing agents include amine type, phenol type, and acid anhydride type.
[0048] When a one-part epoxy resin is used, the time of thermal hardening can be adjusted by the curing treatment (thermal hardening process), enabling efficient batch processing, etc. The curing treatment is carried out, for example, by heating the bonded magnet after the molding process to 130 to 250°C, or even 150 to 230°C.
[0049] Incidentally, each magnet particle may be coated with a surfactant suitable for the resin used. This can improve the orientation variability of the magnet particles in the softened or molten resin, and the bonding between the magnet particles and the resin. When an epoxy resin is used, for example, a titanate coupling agent or a silane coupling agent can be used as the surfactant. The thickness of the surfactant layer may be about 0.1 to 2 μm.
[0050] Bonded Magnets The bonded magnet may have a relative density of, for example, 90% or more, 95% or more, or even 98% or more. The upper limit of the relative density is 99% or even 100%. Note that the relative density (ρ / ρ 0 ) is the theoretical density (ρ 0 ) is the ratio (percentage) of the actual density (ρ) to the theoretical density (ρ 0 ) is determined from the true density of the magnetic powder and binder resin that make up the bonded magnet and the amount of each mixed together. The real density (ρ) is determined from the mass and volume obtained by measuring the bonded magnet after molding (and curing). The volume can be determined by the Archimedes method or calculated from the shape (dimensions) of the molded body.
[0051] The bonded magnet may be magnetized (magnetizing magnetic field: 2 to 6 T) before or after the curing process. The bonded magnet can exhibit a high residual magnetic flux density (Br) of, for example, 0.7 T or more, 0.75 T or more, or even 0.8 T or more.
[0052] The bonded magnet preferably has an irreversible demagnetization rate (100°C x 1000 hours), which is an index of heat resistance or durability, of, for example, within -3%, -2%, or even -1.5%.
[0053] Magnetic Members Bonded magnets are used in a variety of magnetic components. When bonded magnets are molded integrally within the cavity of a housing, the magnetic components can be manufactured efficiently. When bonded magnets are molded at low pressure, deformation of the housing that forms the cavity is suppressed. This increases the design freedom of the housing and improves the precision of the magnetic components. A typical example of such a magnetic component is the field magnet of an electric motor (vehicle drive motors, air conditioners, motors for home appliances, etc.). EXAMPLES
[0054] A number of samples (compression bonded magnets) were produced under different molding conditions, and their properties were measured and evaluated. The present invention will be described in detail below based on these specific examples.
[0055] First Example: Sample Production (1) Magnet powder and binder resin The magnet powders used were a commercially available NdFeB-based anisotropic magnet powder (Magfine, manufactured by Aichi Steel Corporation; Br: 1.28 T, iHc: 1313 kA / m, average particle size: 125 μm), which is a coarse powder produced by hydrogen treatment (d-HDDR), and a commercially available SmFeN-based anisotropic magnet powder (SmFeN alloy fine powder C, manufactured by Sumitomo Metal Mining Co., Ltd.; Br: 1.35 T, iHc: 875 kA / m, average particle size: 3 μm), which is a fine powder.
[0056] As the binder resin, a thermosetting epoxy resin (NC-3000L manufactured by Nippon Kayaku Co., Ltd.) was prepared. The base resin of this resin was a biphenyl type, and the hardener was a phenol type. The softening point of the resin was 60°C.
[0057] (2) Bonded magnet raw materials A bonded magnet raw material was prepared by mixing magnet powder, which was weighed out at a ratio of 8:2 (mass ratio / volume ratio was also almost the same) of coarse powder and fine powder, with binder resin. The magnet powder was 70% by volume (binder resin: 30% by volume) of the total mixture (bonded magnet raw material) of magnet powder (coarse powder and fine powder) and binder resin.
[0058] The magnet powder and the binder resin were mixed for 5 minutes in a non-pressurized state with the kneader rotating at a low speed (10 rpm). At this time, the kneader's temperature was kept at 90° C. In this way, a compound in which the magnet powder and the binder resin were melted and mixed was obtained (melt mixing process).
[0059] (3) Molding The compound was filled into the cavity of the mold (containing process). The temperature of the mold (inner wall surface of the cavity) was kept at 150°C (constant) from the start of molding (before filling) to the end of molding. The compressive force (P) applied to the cavity was either 10 MPa, 20 MPa, or 30 MPa.
[0060] Note that a preformed compound may be used to integrally mold a bonded magnet into the slots of a rotor core, etc. The preformed compound is obtained, for example, by filling a cavity whose cross-sectional shape is slightly smaller than the slots, etc., with the compound and applying pressure (preformed process).
[0061] "No magnetic field molding" where no aligning magnetic field was applied, "constant magnetic field molding" where a constant aligning magnetic field was applied continuously from the start of molding to the end of molding, and "variable magnetic field molding" where the magnetic field was cut off midway through molding were all performed with each compression force. The time from the start of molding (t0: cure degree 0%) when the compound is filled into the cavity (simply called "raw material supply") to the end of molding (t5: cure degree 95%) when the bonded magnet is ejected from the cavity (simply called "molding time") was 5 minutes (see Figure 1B).
[0062] In both cases, the start of compression (t2) was set to 1 minute after the start of molding (when the raw materials were supplied) (within 10% degree of hardening), and the end of compression (t4) was set to 4 minutes after the start of molding (when the raw materials were supplied) (1 minute before the end of molding: when the hardening degree was 70% or more).
[0063] In the constant magnetic field molding and variable magnetic field molding, the application of the aligning magnetic field started (t1) 0.5 minutes after the start of molding (within 5% degree of hardening). In the constant magnetic field molding, the application of the aligning magnetic field ended (t3) 4 minutes after the start of molding (same time as the end of compression: degree of hardening 70% or more).
[0064] In the magnetic field changing molding, the end of the application of the aligning magnetic field (t3) was set 3 minutes after the start of molding (1 minute before the end of compression: hardening degree 35%). In this case, the period before the end of the application of the aligning magnetic field (t2 to t3 or t0 to t3) corresponds to the first molding process, and the period after the end of the application of the aligning magnetic field (t3 to t4 or t3 to t5) corresponds to the second molding process.
[0065] The applied magnetic field was 1.2 T (constant), and the orientation direction was perpendicular (radial direction) to the compression direction (axial direction). The application and interruption of the magnetic field was performed by switching (ON / OFF) the current to the electromagnetic coil.
[0066] Furthermore, the binder resin used in bonded magnets is usually composed of a base resin and a hardener. The base resin and hardener undergo a cross-linking reaction depending on the heat history they are exposed to. The degree of hardening indicates the degree of progress (proportion). Therefore, the "degree of hardening" referred to in this specification is calculated using the following formula. Degree of curing = (total amount of cured resin in the bonded magnet) / (total amount of resin in the bonded magnet) Total amount of cured resin in the bonded magnet = (Total amount of resin in the bonded magnet) - (Amount of dissolved resin (unreacted resin)) Amount of dissolved resin (unreacted resin) = (Total weight of bonded magnet) - (Weight of bonded magnet after immersion in solvent)
[0067] Each weight was determined as follows. First, the total weight of the bonded magnet (test piece) to be measured was measured in advance. The "total amount of resin" in the bonded magnet was calculated from the raw material ratio of magnet powder and binder resin. Next, the bonded magnet was immersed in a solvent (methyl ethyl ketone) to dissolve the uncured (unreacted) base resin and hardener. The "weight of the bonded magnet after immersion in solvent" was determined by weighing the remaining amount after dissolution.
[0068] (4) Cure treatment Each bonded magnet (compression molded body) was removed from the cavity of the mold and heated in air at 150° C. for 30 minutes to thermally cure the binder resin almost completely. Description of magnetization.
[0069] (5) Magnetization Each bonded magnet was magnetized by applying a magnetic field (6 T) using an air-core coil.
[0070] Second Example: Sample Production In the above-mentioned magnetic field change molding, bonded magnets were also manufactured by changing the end time (t3) of the application of the aligning magnetic field in various ways. Specifically, t3 was set to 1.5 minutes (hardening degree 15%), 2.5 minutes (hardening degree 25%), 3 minutes (hardening degree 35%), 3.5 minutes (hardening degree 45%), or 5 minutes (hardening degree 95%) from the start of molding (when the raw material was supplied). Except for the change in t3, the magnetic field change molding was performed in the same manner as in the first embodiment. However, the compression force was set to either 20 MPa or 30 MPa. In this embodiment, the end time of compression (t4) was set to the time when the hardening degree was 70% or more from the start of molding (when the raw material was supplied). Therefore, when t3=5 minutes (hardening degree 95%), it essentially means constant magnetic field molding (t3=t4=t5).
[0071] Measurement and Observation (1) Density The actual density (ρ) of the bonded magnet after curing was calculated using the volume determined from the outer dimensions and the measured mass.
[0072] (2) Magnetic properties The magnetic properties of the bonded magnets were measured at room temperature using a DC BH tracer (TRF-5BH-25Auto, manufactured by Toei Kogyo Co., Ltd.). The residual magnetic flux density (Br) was calculated from the obtained BH curve. The ratio (Br / 4πIs) of the residual magnetic flux density to the saturation magnetization (4πIs) was defined as the degree of orientation.
[0073] "evaluation" Based on the first embodiment, a scatter diagram in which the density of each bonded magnet is plotted for each compression force is shown in Figure 2. Based on the second embodiment, the density, degree of orientation, and residual magnetic flux density of each bonded magnet are shown in Figures 3A and 3B (collectively referred to as "Figure 3"). Figure 3A shows the case where the compression force was 20 MPa, and Figure 3B shows the case where the compression force was 30 MPa.
[0074] As is clear from Figure 2, when the magnetic field-changing compaction was performed, a bonded magnet with a higher density was obtained than when the magnetic field-changing compaction was performed. Furthermore, the density of the bonded magnet obtained by the magnetic field-changing compaction was almost the same as that of the bonded magnet obtained by the magnetic field-free compaction.
[0075] Therefore, it was found that by performing compaction with a modified magnetic field, it was possible to increase the density of the bonded magnet or reduce the compressive force compared to compaction in a magnetic field.
[0076] As is clear from Fig. 3, when performing magnetic field changing molding, it is possible to achieve both high density or high residual magnetic flux density and high degree of orientation by appropriately setting the time (t3) when the application of the aligning magnetic field ends. Based on the second example, the time (t3) when the application of the aligning magnetic field ends (cuts off) is preferably set to 2.5 to 4 minutes (degree of hardening: 25 to 70%) or 3 to 3.5 minutes (degree of hardening: 35 to 45%) after the start of molding (t0).
[0077] Rota By carrying out the above-mentioned magnetic field changing molding, bonded magnets were molded integrally into the slots (cavities) of the rotor core (housing / electromagnetic component) of an embedded permanent magnet synchronous motor (IPM). The appearance of the rotor (field element) thus obtained is shown in Figure 4. The rotor core is made of a laminate of silicon steel sheets punched into the desired shape.
[0078] Because the molding pressure of the bonded magnet was small, there was almost no deformation even in the thin-walled parts on the outer periphery of the slot. Therefore, it was confirmed that the manufacturing method of the present invention can produce a rotor for IPM with high precision (roundness, cylindricity) and a high density and highly oriented bonded magnet.
Claims
1. The method includes a molding step of compressing a bond magnet raw material, which is made of magnet powder and a binder resin capable of binding the magnet powder, in a cavity while heating the bond magnet raw material, The magnet powder includes anisotropic magnet powder, The binder resin includes a thermosetting resin, The bonded magnet raw material has a volume ratio of the magnet powder to the total of the magnet powder and the binder resin of 60 to 80 volume %, The molding step includes a first molding step in which a compressive force is 5 to 50 MPa and an aligning magnetic field is applied to the cavity, and a second molding step in which the aligning magnetic field is reduced or cut off after the first molding step, The second molding step is started when the degree of cure of the thermosetting resin is 25-45%, and is continued until the degree of cure reaches 70% or more.
2. The method for producing a compression bonded magnet according to claim 1, wherein the compressive force in the molding step is 10 to 40 MPa.
3. The method for producing a compressed bonded magnet according to claim 1 or 2, wherein the volume ratio of the bonded magnet raw material is 65 to 75 volume %.
4. 4. The method for producing a compressed bonded magnet according to claim 1, wherein the aligning magnetic field is applied in an orientation direction that intersects with a compression direction of the bonded magnet raw material.
5. A method for manufacturing a compressed bonded magnet as described in any one of claims 1 to 4, wherein heating is continued from the start to the end of the molding process.
6. The method for producing a compression bonded magnet according to any one of claims 1 to 5, wherein the thermosetting resin is an epoxy resin.
7. The method for producing a compressed bonded magnet according to any one of claims 1 to 6, wherein a magnetic member is obtained in which the compressed bonded magnet is integrated into a case having the cavity.
Citation Information
Patent Citations
Manufacture of anisotropic bonded magnet
JP1991190208A
Manufacture of magnetic anisotropy resin bonding type magnet and magnetic anisotropy resin type magnet
JP1996031677A
Device and method for manufacturing magnet member
JP2020156203A